Targeting toll-like receptors: unveiling potential therapeutic strategies for deep vein thrombosis - Shao, Wei; Wang, Zilong; Wu, Jian; Guo, Tianting; Mo, Jianwen (Frontiers in Immunology, 2025)
Deep vein thrombosis (DVT) is a complex multifactorial vascular disease characterized by abnormal blood stasis and coagulation within the deep veins, primarily occurring in the lower limbs. This pathological condition not only causes local circulatory disruption but also has the potential to trigger life-threatening pulmonary embolism through thrombus detachment, thus posing a major threat to human health. Toll - like receptors (TLRs), essential components of the innate immune system, have been increasingly acknowledged as crucial determinants in the pathogenesis of DVT. TLRs possess the ability to recognize a diverse range of pathogen - associated molecular patterns (PAMPs) and endogenous danger - associated molecular patterns (DAMPs). Upon activation, they trigger a cascade of inflammatory responses that are intricately intertwined with the thrombotic process. This review comprehensively scrutinizes the extant knowledge pertaining to the role of TLRs in DVT. It systematically synthesizes the molecular mechanisms underpinning the participation of TLRs in DVT, spanning platelet activation, endothelial cell dysfunction, and leukocyte recruitment. Moreover, it delves profoundly into the potential of targeting TLRs as therapeutic strategies for DVT. This entails the exploration of the development and application of TLR inhibitors or antagonists. By elucidating these aspects, the objective is to proffer novel perspectives and insights for the prevention and treatment of DVT.